Attachment in intellectual and developmental disability : a clinician's guide to research and practice - Fletcher, Helen K.; Flood, Andrea; Hare, Dougal Julian (Chichester, West Sussex, UK : Wiley Blackwell, 2016)
'Attachment in Intellectual and Developmental Disability: A Clinician's Guide to Practice and Research is the first book to explore the clinical difficulties associated with attachment relationships in people with intellectual and developmental disabilities. Draws together knowledge from disparate sources in a definitive new resource for clinicians working in this area A growing body of evidence-based approaches in this area are underpinned by attachment theory, including direct intervention and the use of attachment theory to understand interactions and relationships Presents and integrates cutting-edge models and approaches that have previously been available only to specialists Written by mainstream practitioners who are active in clinical work and research; focused on real-world applications, with illustrative case examples throughout'--
Includes index.
Online resource; title from PDF title page (John Wiley, viewed March 22, 2016).
Keywords: Attachment behavior; Attachment disorder; Mental retardation; Electronic books